Do Economic Crises Always Undermine Trust in Others? The Case of Generalized, Interpersonal, and In-Group Trust - Navarro-Carrillo, Ginés; Valor-Segura, Inmaculada; Lozano, Luis M.; Moya, Miguel (Frontiers in Psychology, 2018)
After the global economic collapse triggered by the Great Recession, there has been an increased interest in the potential psychological implications of periods of economic decline. Recent evidence suggests that negative personal experiences linked to the economic crisis may lead to diminished generalized trust (i.e., the belief that most of the people of the society are honest and can be trusted). Adding to the growing literature on the psychological consequences of the economic crisis, we propose that the perceived personal impact of the economic crisis not only would undermine generalized trust but also may lead to increased interpersonal trust (i.e., directed to specific and close people) and depersonalized in-group trust (i.e., directed to individuals who, while strangers, belong to the same group [e.g., social class]). Across three studies (N = 1379), we tested these central hypotheses and ascertained whether the perceived personal impact of the crisis would predict these types of trust (assessed using questionnaire and behavioral measures) independent of individuals’ socioeconomic status. Non-experimental data from Study 1 revealed that a higher perceived personal impact of the crisis is related to lower levels of generalized trust and higher levels of interpersonal trust. These effects were independent of participants’ socioeconomic status. Non-experimental data from Study 2 replicated the findings obtained in Study 1 and also showed a positive association between the perceived personal impact of the crisis and depersonalized in-group trust. This pattern of results emerged even after controlling for socioeconomic status, gender, age, political orientation, religiosity, and unemployment status. In Study 3, using an experimental design, we found that the salience of a possible economic downturn led to decreased generalized trust and increased interpersonal and depersonalized in-group trust—independently of socioeconomic status—compared with the control condition. These results challenge the conventional wisdom that economic crises invariably undermine trust in others. The implications of the present research as well as future research directions are discussed.